2017
DOI: 10.12776/qip.v21i3.1024
|View full text |Cite
|
Sign up to set email alerts
|

The Reasons for Decertification of ISO 9001: Financial Aspects

Abstract: <p><strong>Purpose:</strong> The purpose of this paper is to analyse the financial performance of organizations that give up their QMS (Quality Management System) according to ISO 9001 certification. Different reasons found for the cancellation of ISO 9001 certification were taken into consideration. The decrease in certification of ISO 9001 standard is, during the past few years, noticeable in many countries. Therefore, there is a need to analyze the phenomena.</p><p><strong&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
9
1
1
Order By: Relevance
“…Meanwhile Aba et al (2016) concluded that certified companies are better than non-certified companies. Kafel and Simon (2017) found different research results from previous studies that the ISO 9001 certified company has nothing to do with financial performance. Furthermore, Hendricks and Singhal (1996) and Hendricks and Singhal (2001) who examined ISO on long-term stock reactions.…”
Section: Introductioncontrasting
confidence: 75%
“…Meanwhile Aba et al (2016) concluded that certified companies are better than non-certified companies. Kafel and Simon (2017) found different research results from previous studies that the ISO 9001 certified company has nothing to do with financial performance. Furthermore, Hendricks and Singhal (1996) and Hendricks and Singhal (2001) who examined ISO on long-term stock reactions.…”
Section: Introductioncontrasting
confidence: 75%
“…These decertification decisions by individual organizations aggregate to detectable macro-level trends. For instance, worldwide certifications of ISO 9001 decreased for the first time in 2011 (Kafel and Simon, 2017). Mastrogiacomo et al (2021) further highlight that the European diffusion of ISO 9001 reached its highpoint in 2010 at 530,039 certifications and has steadily decreased in subsequent years to only 387,836 certifications in 2017; in fact, 2017 exhibited a downward trend in certifications for all the world's regions except 'East Asia and the Pacific'.…”
Section: Introductionmentioning
confidence: 94%
“…Los motivos de que la ISO 9001 haya dejado atrás la fase de crecimiento puede estar en el abandono de las certificaciones, pero también en las barreras de entrada o en la reducción del atractivo para las restantes empresas no certificadas (Zimon y Dellana, 2019;Simon y Kafel, 2018;Cândido et al, 2019;Kafel y Simon, 2017;Sansalvador y Brotins, 2015). Profundizando en ese ámbito, otros trabajos analizan el impacto que tienen sobre las empresas la cancelación de esta certificación (Alič, 2014;Cândido et al 2016).…”
Section: Certificaciones Iso 9001 Y "Q De Calidad" En El Sector Alojamiento Y Restauración Españolunclassified